APPLICATION OF DEMONSTRATION METHODS WITH TRADITIONAL GAME SETANGGA GUNUNG TO IMPROVE THE INTELLIGENCE AND RELATED MOTORCYCLES OF CHILDREN (Study in Group B TK Melati DW II South Bengkulu) - Rudisnawati Rudisnawati; Nina Kurniah (UNIB Press, 2018)
The purpose of the study was to describe the application of traditional game Setangga gunung in increasing the precision and gross motorik of children in the B3 group in Melati DW II Kindergarten in South Bengkulu Regency. This study uses Classroom Action Research (CAR). The subjects of this study were 15 B3 children in Melati DW II Kindergarten, South Bengkulu Regency, totaling 15 people. Data collection techniques used teacher observation sheets and children's observation sheets, namely accuracy and gross motorik. Analysis of research data using the mean test and t test. The results showed that there was a significant difference between the accuracy and gross motorik of children between cycle 1 and cycle 2. The results of cycle 3 showed that the teacher had succeeded in 100% carrying out the demonstration method and the application of demonstration methods with mountain support game could increase the precision and gross motoric age of children early.